2009
DOI: 10.1111/j.1365-3156.2009.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic smoke exposure is associated with alveolar macrophage particulate load

Abstract: Summaryobjectives Indoor air pollution is associated with impaired respiratory health. The pre-dominant indoor air pollutant to which two billion of the world's population is exposed is biomass fuel smoke. We tested the hypothesis that reported smoke exposure in men and women is associated with increased alveolar macrophage uptake of biomass smoke particulates.methods Healthy volunteers attending for research bronchoscopy in Malawi completed a questionnaire assessment of smoke exposure. Particulate matter visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…First, in rats there is a strong association between AM carbon and long-term inhaled BC dose [12]. Secondly, in Malawian adults we found that AM carbon tracks closely with the BC-generating potential of the fuel regularly used in the home for cooking [30]. Thirdly, the lifespan of AM in the lower airway, and therefore its ability to acquire inhaled BC, is up to several months [31].…”
Section: Discussionmentioning
confidence: 75%
“…First, in rats there is a strong association between AM carbon and long-term inhaled BC dose [12]. Secondly, in Malawian adults we found that AM carbon tracks closely with the BC-generating potential of the fuel regularly used in the home for cooking [30]. Thirdly, the lifespan of AM in the lower airway, and therefore its ability to acquire inhaled BC, is up to several months [31].…”
Section: Discussionmentioning
confidence: 75%
“…9 Lam (2013) found the gap between lighting and cooking to be smaller than this. Fullerton et al (2009) found higher levels of particulate matter associated with macrophage cells in people living with kerosene lamps, particularly simple wick-based lamps but also with hurricane lanterns and candles, which have particularly incomplete combustion.…”
Section: Indoor Air Pollutionmentioning
confidence: 95%
“…45 One of the most important roles of macrophages in the lungs of smokers is clearing the particles entered the lungs through tobacco smoking. 46 In this regard, it is of interest to assess the effects of tobacco smoke on phagocytic capacity of macrophages. Accordingly, macrophages isolated from the lungs of smoke-exposed mice were found to have decreased capacity to bind and internalize yeasts.…”
Section: Discussionmentioning
confidence: 99%